The problem of recognizing the intentionality of actions in the identification of manifestations of social irresponsibility of an enterprise - Sokołowska-Durkalec, Agnieszka; Zajbert, Edyta (Problem rozpoznania intencjonalności działań w identyfikacji przejawów społecznej nieodpowiedzialności przedsiębiorstwa, 2019)
The issue of the relationship between the intentionality of actions and the manifestations of social irresponsibility of enterprise is rarely explored in both the domestic and international literature on the subject. Therefore, it is difficult to overestimate the role of indicating key problems in several perspectives (theoretical, methodological, empirical and practical) in identifying the intentionality of actions in the manifestations of social irresponsibility of enterprise. The purpose of this epistemological article is to highlight the multidimensional problem of recognizing the intentionality of actions in identifying the manifestations of social irresponsibility of enterprise. Based on a review of the literature on the subject, an attempt was made to define the concept of the intentionality of actions, embedding the problem of the intentionality of actions in the concept of corporate social irresponsibility, and also to point out the key issues constituting the problem of recognizing the intentionality of actions in identifying the manifestations of social irresponsibility of enterprise
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 196-206